Spending for Development : Making the Most of Indonesia's New Opportunities, Indonesia Public Expenditure Review 2007 - World Bank (Washington, DC, 2012)
This Public Expenditure Review (PER) 2007 examines and explains some of the constraints facing the government in public resource management and allocation, and offers recommendations for improvements in six critical areas: fiscal space, education, health, infrastructure, public financial management and decentralization. Although Indonesia has made important progress in reforming its public finances and increasing transparency, Indonesia's reform agenda, as highlighted by the PER, is far from complete. Equity and efficiency of spending remain major issues, for instance finding an optimal allocation of resources that reflects development priorities, and achieving an annual spending pattern that is no longer strongly skewed towards the end of the financial year. This report tries to establish the facts about Indonesia's public expenditures, presenting trends over time and analyzing the composition across sectors and levels of government. It presents comprehensive information on key sectors, including sub-national governments and state-owned enterprises in key infrastructure sectors. Based on these facts, the report asks: Who benefits from these substantial amounts of public resources? Where are the gaps? Which regions are well-endowed? Which regions are lagging behind? In addition to these questions, this report also tries to respond to key concerns that are in the minds of many ordinary Indonesians and friends of Indonesia, such as: Can Indonesia afford to spend more? Is the current level of education and health spending sufficient? How to revitalize infrastructure investment, and which sectors are the priorities? Why is it so difficult to disburse funds through the government budget system? How unequal is Indonesia and how should fiscal transfers be structured to equalize disparities? This report addresses seven critical expenditure areas. The first two chapters (Chapter 1 on fiscal space and Chapter 2 on cross-sectoral allocations) discuss how much money is available to the government and how it is allocated across sectors and levels of government. The following three chapters on education, health, and infrastructure analyze how resources are currently allocated within these critical sectors and how effectively they are used. The final two chapters (Chapter 6 on public financial management and Chapter 7 on decentralization) highlight institutional and crosscutting issues in effective public expenditure management.